On the acyclicity of fixed point sets of multivalued maps - Gabor, Grzegorz (Topological Methods in Nonlinear Analysis, 1999)
The paper is devoted to studying a topological structure of sets of fixed points (or equilibria) of some classes of single-valued or multivalued maps. In our opinion, this paper contains all main results connected with this problem. We deal with Browder-Gupta type results and the inverse systems approach.